Immuno-ophthalmology - Pleyer, Uwe 1957-; Zierhut, Manfred 1953-2022; Behrens-Baumann, Wolfgang (Karger, 1999)
Although considerable light has been shed on the mechanisms of ocular immunity over the past 20 years, a complete understanding still eludes our grasp. To many ophthalmologists immunology itself is a comparatively new field. This volume will bring the latest findings in immunological research and the resulting new therapy methods to the ophthalmologist in practice. The scope of the topics goes from general principles of immuno-ophthalmology to more specific ones such as immunology of corneal transplantation or immune regulation of uveoretinal inflammation.With its broad scope of contributions, this publication will not only be significant to the ophthalmologist, but also to pediatricians, specialists in internal medicine as well as dermatologists confronted with eye diseases
Keywords: Ophthalmology; Immunology; Allergy; Immunosuppression; Pharmacology; Transplantation; Immuntherapie; Immunpathologie; Augenkrankheit; Aufsatzsammlung